Field monitoring and response characteristics of longitudinal movements of expansion joints in long-span suspension bridges. (1st October 2020) - Hu, Jianhua; Wang, Lianhua; Song, Xiaopeng; Sun, Zhanghong; Cui, Jianfeng; Huang, Guoping
Highlights: The field monitoring results of the longitudinal movement was described in detail. The spectral characteristics of the movement of the expansion joint were revealed. The contributions of movement components to the total longitudinal movement response were clarified. The effects of the central buckle on the longitudinal movement response were discussed. Abstract: The longitudinal movement of the expansion joint affects the wear of the bearing and the fatigue damage of the expansion joint itself. A long-term monitoring on a long-span suspension bridge has been set up to reveal the mechanism and the response characteristic of the longitudinal movement of the expansion joint. This paper presents the field measurement results and analysis of the longitudinal movement. The results show that the temperature variation results in the fluctuation of the longitudinal movement of the expansion joint. Whereas, the high-frequency components are dominated by the vehicle and ambient excitations. Moreover, the RMS movement and the temperature show a significant linear relationship. Then, the frequency-domain analysis is performed to investigate the spectral characteristic of the longitudinal movement. It is shown that the quasi-static effect of the vehicle governs the longitudinal movement at 10-min interval, and the dynamic effect of the vehicle plays an important role in the cumulative movement of the expansion joint. At last, the sway vibration of the girder is discussed through the finite element model of the suspension bridge, and the effects of the central buckle on the longitudinal movement of the expansion joint are investigated.